EFFECTIVENESS OF STRATEGY IMPLEMENTATION APPROACHES IN GERMAN MULTINATIONAL COMPANIES IN THE SOFTWARE INDUSTRY: A CASE STUDY OF SAP SE - Koleva, Stela (Digital Repository of Theses - SSBM Geneva, 2022)
Various approaches to aiding multinational companies (MNCs) in the strategyimplementation process have been suggested. However, MNCs in the software industry, such as the German company SAP SE, operate in a diverse, dynamic, and challenging environment that can make effective strategy implementation difficult. This study aims to determine which of several strategy-implementation methods is most effective for SAP SE: the commander approach, the organizational-change approach, the collaborative approach, or the cultural approach. The researcher addresses the research questions using qualitative research based on a descriptive research design, collecting primary data from the top managers in SAP SE. A total of 58 participants engaged in the study’s structured questionnaire (n = 51) and interview (n = 7). While the collaborative approach to strategy implementation is dominant, this research shows significant differences in effectiveness between the collaborative approach and both the commander approach (P = 0.022) and the organizational-change approach (P = 0.035). Likewise, differences in effectiveness exist between the cultural approach and the commander approach (P = 0.024). This study also describes various challenges in using the highlighted strategy-implementation tactics, suggesting through its outcome that a combined approach best enables managers to address difficulties as they arise. This study suggests that managers of MNCs in the software industry consider adopting a collaborative approach as a means of creating synergy across units and locations. A combined approach could also address the challenges faced during strategy implementation.